A new quasi‐Z‐source switched‐boost four‐switch three‐phase inverter with independent shoot‐through and non‐shoot‐through modulation indexes. Issue 3 (28th January 2021) - Babaee Vandishi, Mohammad; Lahooti Eshkevari, Alireza; Salemnia, Ahmad; Mosallanejad, Ali
Abstract: Four‐switch three‐phase inverters (FSTPI) are the cost‐optimised version of two‐level voltage source inverters (TL‐VSI), promoted for low‐power/low‐voltage machine drive systems. Adding impedance‐based networks to the input of conventional VSIs provides both step‐up and step‐down features; however, the shoot‐through (ST) modulation index limits the maximum attainable modulation index. Furthermore, in FSTPI, one switching leg has two series capacitors instead of power switches. Therefore, they are exposed to the voltage imbalance problem. This paper proposes a novel step‐up FSTPI with independent shoot‐through and non‐shoot‐through (NST) modulation indexes, improved boost factor, continuous input current, and high efficiency. This topology incorporates a quasi‐z‐source switched‐boost network with independent power switches and three duty ratios that affords two active states and one shoot‐through event. These features enhance the performance of this topology if compared with former FSTPI and quasi‐z‐source FSTPI. For evaluating the performance of this topology, simulation in MATLAB software and experiment on a prototype have been done. Simulation and experimentation results confirm the proposed topology.